O papel da ciclooxigenase-2 da pressão arterial na lesão renal de ratos submetidos à infusão contínua de angiotensina II - Santin, Flávia; Vailati, Maria do Carmo Fernandez [UNESP]; Rodrigues, Marcela Marcondes Pinto [UNESP]; Michelucci, David; Martin, Luis Cuadrado [UNESP]; Schwartz, Denise Saretta (FapUNIFESP (SciELO), 2010)
Angiotensin II (ANGII) is a vasoconstrictor which action on inflammation has been studied. The objective of this study was to verify the stimulation of cyclooxigenase-2 and blood pressure on renal damage by ANGII. Wistar rats were distributed into four groups, as follows: group 1 – control; group 2 – ANGII; group 3 – ANGII + celecoxib; and group 4 – celecoxib. The ANGII was infused in the animals by subcutaneous osmotic mini-pumps during 72 hours. After that, euthanasia was performed. The blood pressure was measured before the drugs administration and before the euthanasia. Histopathological and immunohistochemical evaluations were performed in kidneys to assess the expression of COX-2. It was concluded that ANGII caused renal damage, regardless of blood pressure values. ANGII associated with celeboxib increased blood pressure. Celecoxib did not protect the kidneys against ANGII activities.

A angiotensina II (ANGII) é um vasoconstritor, entretanto, sua atuação na inflamação tem sido estudada. Objetivou-se verificar o estímulo da ciclooxigenase-2 e da pressão arterial na lesão renal por ANGII. Para tanto, utilizaram-se ratos Wistar, distribuídos no grupo 1: controle, grupo 2: ANGII, grupo 3: ANGII + celecoxibe, grupo 4: celecoxibe. A ANGII foi administrada via minibomba no subcutâneo dos animais durante 72 horas, sendo então realizada a eutanásia. A pressão arterial foi aferida antes da administração dos fármacos e antes da eutanásia. Colheram-se os rins dos animais para histopatologia e para imunoistoquímica, avaliando-se a expressão de COX-2. Concluiu-se que a ANGII promoveu lesões renais, independentemente dos valores da pressão arterial; ANGII associada ao celecoxibe levou ao aumento da pressão arterial. O celecoxibe não protegeu os rins contra as ações da angiotensina II.
The role of cyclooxigenase-2 and blood pressure on the kidney damage in rats submitted to continuous infusion of angiotensin II
Keywords: Blood pressure; Celecoxib; Nephrotoxicity; Celecoxibe; Nefrotoxicidade; Pressão arterial